HISTORY AND TYPES OF FOLK PERFORMANCE ART (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
In this article, the history, types, development and protection of the intangible cultural heritage of Uzbekistan's folk art, the organization of national performance art in history, and various celebrations and public events in order to ensure its traditionality are described as intangible cultural heritage. it is said that special attention is paid to the preservation of heritage.